Bacterial nanocellulose (BNC) biosynthesis by Komagataeibacter hansenii RM-03 using agricultural waste as substrates and BNC-silver nanocomposite preparation - Daud, Aini Darwina; Abdul Rahman, Nor’Aini; Foo, Hooi Ling; Mohamad, Rosfarizan (University of Malaya, 2024)
Bacterial nanocellulose (BNC) is a remarkable biopolymer synthesised by bacterium, exhibiting exceptional properties. However, conventional Hestrin-Schramm (HS) medium, particularly the carbon source, poses challenges of high costs and low productivity. This study explores BNC biosynthesis on a modified HS medium, employing agricultural wastes (sugarcane molasses, banana peel, and pineapple peel) as carbon sources, and compares the overall yield of BNC produced. Sugarcane molasses proved to be the most effective, yielding the highest BNC concentration (8.19 g/L) after 7 days, followed by pineapple peel (2.16 g/L) and banana peel (2.11 g/L). Extensive research was conducted to enhance properties of BNC by an environmentally friendly approach, incorporating silver nanoparticles (AgNP) utilising Momordica charantia fruit extract, resulting in a BNC-Ag nanocomposite. The synthesis involved mixing 1 mM silver nitrate (AgNO3) with 15 mL of M. charantia fruit extract to reduce Ag ions to AgNP, which was confirmed by UV-vis spectroscopy with an absorbance peak between 400 and 410 nm. Characterisation using FESEM and TEM on the synthesized BNC showed minimal impact on BNC fiber diameter from waste-derived carbon sources. XRD indicated slight variations in crystallinity index, with the highest (85%) in TSM-derived BNC. FTIR analysis revealed similar chemical profiles across all BNC, indicating cellulose formation. The BNC-Ag nanocomposite exhibited potent antibacterial activity against multi-drug resistant strains (Pseudomonas aeruginosa, Salmonella typhi, Bacillus subtilis, Staphylococcus aureus) through disc diffusion method with inhibition zones up to 16.8 mm. Overall, the findings from this study contribute to the development of environmentally sustainable for the production of functional BNC materials with enhanced properties for diverse applications.